Perbandingan Kebijakan Pendidikan antara Negara Korea Selatan dan Korea Utara - Hindun Qurrotu Aini; Abdal Malik Fajar Alam (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
This research provides a deeper understanding of significant differences in educational approaches and their impact on human resource development in both Koreas. Education is crucial and a primary focus in every country's issues, as the level of education often determines a nation's advancement. The majority of countries mandate their residents to experience and acquire education within a specified timeframe. South Korea and North Korea originated from one country, but the influence of two major world blocs led to the division of Korea into two parts, the South and the North. This study aims to compare the education systems between South Korea and North Korea. South Korea, embracing liberalism and employing a democratic governance system, has managed to establish itself as one of the countries with the best education systems globally, contributing to its status as an advanced nation. On the other hand, North Korea, adhering to communism and employing an authoritarian government system, restricts social mobility and knowledge dissemination. The research methodology employed is qualitative, utilizing a descriptive comparative approach through literature review. The findings reveal that education in South Korea is highly organized, ranging from institutions like KICE to programs initiated by KOICA. Human resources from South Korea tend to excel in various sectors. Meanwhile, North Korea's education system focuses on ideology, with a lack of academic freedom impacting the quality of human resources. Consequently, human resources from North Korea are categorized as low quality. In an effort to improve the quality of education, it must go hand in hand with the improvement of the human resources' quality in a country so that the people living within it can have a decent life.